Methods of interpretation analysis of the orthodox liturgical chants - Voskoboinikova, Yuliia; Voskoboinikova, V. (My University, 2021)
У сучасній науці проблема тлумачення православної сакральної музики полягає переважно розглядаються в загальних аспектах на основі культурних, теологічних та музикознавчий контекст. Однак важливо більше уваги приділяти конкретному методи проведення аналізу робіт до їх виконання, особливо коли ми говоримо про літургійну діяльність. На наш погляд, такими методами можуть бути: текстові аналіз; контекстний аналіз; порівняльний аналіз; хоровий аналіз; аналіз форма і фактура; аналіз художньо-виразних засобів; визначення обмежень інтерпретація під час літургійного виконання.

In modern science the problem of interpreting Orthodox sacred music is mainly considered in general aspects based on cultural, theological and musicological contexts. However, it is important to pay more attention to specific methods of performing analysis of works before they are performed, especially when we talk about liturgical performance. In our opinion, such methods can be: textual analysis; contextual analysis; comparative analysis; choral analysis; analysis of the form and texture; analysis of artistic expressive means; definition of restrictions of interpretation during the liturgical performance.
Keywords: музика православна, orthodox music